THE INFLUENCE OF ONLINE-BASED NEW STUDENT ADMISSION SERVICES ON STUDENT SATISFACTION AT MADRASAH ALIYAH NEGERI 3 PEKANBARU CITY - Andriani, Tuti; Purnama, Ade (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to find out how much influence online-based new student admission services have on student satisfaction at MAN 3 Pekanbaru City. This research includes correlation research consisting of online-based PPDB service variables (X) and student satisfaction variables (Y). The methodology in this research is quantitative. The population used in this research was all students at Madrasah Aliyah Negeri 3 Pekanbaru City, totaling 835 people. Because the population was large, the researchers took 105 people to be respondents. This sampling technique uses a systematic sampling technique. The data collection techniques used were questionnaires and documentation. This research data was analyzed using quantitative percentages and simple regression analysis. Based on the research results, it shows that 1) the level of online-based admissions services for new students, namely 83%, is classified as very good, 2) the level of student satisfaction, namely 70.6%, is classified as good, 3) there is a positive influence between online-based PPDB services on student satisfaction in Madrasas. Aliyah Negeri 3 Pekanbaru City with a correlation value of 10,203. This is proven by the correlation test with a Tcount value of 10.208 which is greater than Ttable at the 5% significance level, namely 1.986 (10.208>1.986). The calculation result of the coefficient of determination R square is 0.503. This shows that the influence of online-based new student admission services on student satisfaction at Madrasah Aliyah Negeri 3 Pekanbaru City is 50.3% while the remaining 49.7% is influenced by other variables not included in this research. So, the better the online-based student admission service, the higher the level of student satisfaction.